Causal association between inflammatory bowel disease and acute pancreatitis: a two-sample bidirectional mendelian randomization study - Zhang, Cong; Fan, Xiujing; Li, Zhijun; Hu, Zongyi; He, Chengcheng; Wang, Shanping; Li, Mingsong (Frontiers in Genetics, 2024)
Background: Acute pancreatitis (AP) is an extraintestinal manifestation of inflammatory bowel disease (IBD). Numerous observational studies have reported an increased risk of AP in patients diagnosed with IBD. However, the causal association and directionality between IBD or its subtypes and the development of AP remains unclear due to the limitations of observational research. This study aims to explore the relationship between IBD or its subtypes and AP risk using Mendelian Randomization (MR) method. Methods: A two-sample bidirectional MR study was conducted, selecting genetic variants associated with IBD and AP as instrumental variables from the International Inflammatory Bowel Disease Genetics Consortium (IIBDGC) and FinnGen databases, respectively. The inverse variance weighted (IVW) method used as the primary approach for causal inference. The Cochran Q test was employed for heterogeneity assessment. Sensitivity analyses were performed using the MR Egger intercept test, MR-Presso, and Leave-one-out method. Results: The results revealed that IBD (OR = 1.049, 95% CI = 1.010-1.090, P = 0.013) and ulcerative colitis (UC) (OR = 1.057, 95% CI = 1.013-1.102, P = 0.011) were significantly associated with an increased risk of AP. However, Crohn's disease (CD) (OR = 1.023, 95% CI = 0.993-1.055, P = 0.134) did not show a causal association with the risk of AP. Interestingly, AP was suggestively associated with a decreased risk of CD (OR = 0.797, 95% CI = 0.637-0.997, P = 0.047). Furthermore, there was no causal association between AP and the risk of IBD (OR = 0.886, 95% CI = 0.753-1.042, P = 0.144) or UC (OR = 0.947, 95% CI = 0.773-1.159, P = 0.595). Conclusion: In conclusion, this study provides genetic evidence supporting the causal influence of IBD (specifically UC) on AP, while CD does not appear to have a causal impact on AP.